Theoretical Frameworks in Focus: Group Work Research in Project-Based CS Education - Mikko Kokkoniemi; Ville Isomöttönen (Informatics in Education)
This study builds on a recent systematic mapping of computing education literature by conducting an in-depth qualitative analysis of selected studies on group work in Project-Based Learning (PjBL), published between 2010 and 2021. We examined how prominent theoretical frameworks are used in this context. We found that frameworks were often applied either as teaching tools or to inform course design, and when used in these ways, authors frequently reported positive pedagogical outcomes. While frameworks like Tuckman’s model were often referenced only superficially, Social Loafing was more commonly explored in depth. Inductive analysis was particularly effective in distinguishing between background mentions and more substantial integration of theory.We recommend a more intentional, theory-driven approach to research and pedagogy to strengthen conceptual clarity and practical impact. Shared community resources and clearer reporting practices could further support deeper theoretical engagement in the field.